2015
DOI: 10.1116/1.4937727
|View full text |Cite
|
Sign up to set email alerts
|

Flexible antibacterial Zr-Cu-N thin films resistant to cracking

Abstract: This study investigates how the Cu concentration in Zr-Cu-N films affects the films' antibacterial capacity and mechanical properties. Zr-Cu-N films were prepared by reactive magnetron sputtering from composed Zr/Cu targets using a dual magnetron in an Ar + N2 mixture. The antibacterial capacity of Zr-Cu-N films was tested on Escherichia coli (E. coli) bacteria. The mechanical properties of Zr-Cu-N films were determined from the load vs. displacement curves measured using a Fisherscope H 100 microhardness test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Moreover, when such coatings are deposited on flexible substrates, they easily crack and/or delaminate due to the residual stress resulting from the growth mode (for some reviews on thin film growth modes and on the effect on surfaces, see for instance [119,120]). This issue has recently been investigated for antibacterial films prepared by reactive magnetron sputtering for Cr-Cu-O [44,118], Al-Cu-N [44,114] and Zr-Cu-N [121], where the influence of Cu content on the mechanical and bactericidal properties of the film have been measured. The mechanical characteristics measured through Vickers tests were the film hardness H, defined as its resistance to local plastic deformation [122], the elastic recovery We, defined as the fraction of a given deformation of a solid which behaves elastically [123], the Young's modulus E and the effective Young's modulus E* = E(1 − ν 2 ), where ν = Poisson ratio has been obtained by mechanical indentation.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, when such coatings are deposited on flexible substrates, they easily crack and/or delaminate due to the residual stress resulting from the growth mode (for some reviews on thin film growth modes and on the effect on surfaces, see for instance [119,120]). This issue has recently been investigated for antibacterial films prepared by reactive magnetron sputtering for Cr-Cu-O [44,118], Al-Cu-N [44,114] and Zr-Cu-N [121], where the influence of Cu content on the mechanical and bactericidal properties of the film have been measured. The mechanical characteristics measured through Vickers tests were the film hardness H, defined as its resistance to local plastic deformation [122], the elastic recovery We, defined as the fraction of a given deformation of a solid which behaves elastically [123], the Young's modulus E and the effective Young's modulus E* = E(1 − ν 2 ), where ν = Poisson ratio has been obtained by mechanical indentation.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…The Zr-Cu-N coatings exhibit a ratio H/E* ≥ 0.1, a value indicating an enhanced resistance to cracking for all Cu contents ranging from 0 to 19 at.% Cu. [121] Moreover, the hardness H ranging from~25 to~17 GPa is quite high and it makes it possible to prevent the coating from being removed from the surface of a substrate by fretting (wear). The region of Cu content in which the coatings exhibit a killing of the E. coli bacteria of 100% is marked by dashed lines and in light gray, setting the limit for the minimum Cu concentration in such films [121].…”
Section: Magnetron Sputteringmentioning
confidence: 99%
See 1 more Smart Citation
“…For antibacterial coatings, a long lifetime is a key requirement in many practical applications when these coatings are deposited on contact surfaces of rigid or flexible substrates and must simultaneously exhibit two functions: antibacterial and protective. Recently, it has been shown that flexible antibacterial coatings can provide good mechanical protection of substrates [ 34 , 35 , 36 , 37 , 38 ]. The formation of antibacterial coatings with a high efficiency of killing of bacteria that simultaneously demonstrates good mechanical properties is, however, quite a difficult task [ 13 , 24 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The drastic effect of extremely low amounts of Cu released during the bacterial inactivation can be rationalized by the high toxicity of Cu(Cu(I)/Cu(II) species/oxides on the bacteria and cannot be ascribed to any doping of the TiO 2 by Cu, which requires much higher Cu-amounts. Recent developments on flexible antibacterial sputtered coatings have been reported using Cu as a bactericide agent in the composite films [182][183][184].…”
Section: Interfacial Charge Transfer (Ifct) Suggested On Tio2-cu Filmmentioning
confidence: 99%